The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.3201/eid1209.041344
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impact of Antiviral Drug Use during Influenza Pandemic

Abstract: The recent spread of highly pathogenic strains of avian influenza has highlighted the threat posed by pandemic influenza. In the early phases of a pandemic, the only treatment available would be neuraminidase inhibitors, which many countries are considering stockpiling for pandemic use. We estimate the effect on hospitalization rates of using different antiviral stockpile sizes to treat infection. We estimate that stockpiles that cover 20%-25% of the population would be sufficient to treat most of the clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
175
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(188 citation statements)
references
References 23 publications
9
175
0
4
Order By: Relevance
“…We evaluated the role of intervention strategies incorporated in preparedness plans for the US, the United Kingdom (UK) and the Netherlands. We discuss the potential role of the different intervention strategies and compare our results with those reported in previous studies (van Genugten et al 2003;Longini et al 2004;Gani et al 2005;.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…We evaluated the role of intervention strategies incorporated in preparedness plans for the US, the United Kingdom (UK) and the Netherlands. We discuss the potential role of the different intervention strategies and compare our results with those reported in previous studies (van Genugten et al 2003;Longini et al 2004;Gani et al 2005;.…”
Section: Introductionsupporting
confidence: 59%
“…In the optimistic scenario, we assume high antiviral efficacy and coverage rates (upper-bound parameters in table 2). Similarly, the less optimistic scenario assumes lower-bound parameter values for the antiviral efficacy and coverage (Gani et al 2005) and the Netherlands (van Genugten et al 2002(van Genugten et al , 2003. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Piecewise Linear Number of Infected Figure 2 plots the attack rate, p, which is directly proportional to the total number infected, T (f ), as a function of the fraction of initially exposed individuals, I 0 and reasonable values of R 0 for influenza transmission (Gani et al, 2005). If there are few that are initially infected due to exogenous exposure (small I 0 /S 0 ), then Appendix B justifies the following piecewise linear approximation for T (f ).…”
Section: System Settingmentioning
confidence: 99%
“…Past studies have estimated the reproduction number of individual influenza seasons, in particular for pandemics [11][12][13][14][15][16][17][18][19]. However, no study has yet reported estimates of the reproduction number for several countries and consecutive influenza seasons in the interpandemic period, where a fraction of the population is immune due to previous influenza exposure or vaccination.…”
Section: Introductionmentioning
confidence: 99%